The effect of the DISC1 Ser704Cys polymorphism on striatal dopamine synthesis capacity: an [18F]-DOPA PET study. (26th June 2018) - Dahoun, Tarik; Pardiñas, Antonio F; Veronese, Mattia; Bloomfield, Michael A P; Jauhar, Sameer; Bonoldi, Ilaria; Froudist-Walsh, Sean; Nosarti, Chiara; Korth, Carsten; Hennah, William; Walters, James; Prata, Diana; et al.
Abstract: Whilst the role of the Disrupted-in-Schizophrenia 1 ( DISC1 ) gene in the aetiology of major mental illnesses is debated, the characterization of its function lends it credibility as a candidate. A key aspect of this functional characterization is the determination of the role of common non-synonymous polymorphisms on normal variation within these functions. The common allele (A) of the DISC1 single-nucleotide polymorphism (SNP) rs821616 encodes a serine (ser) at the Ser704Cys polymorphism, and has been shown to increase the phosphorylation of extracellular signal-regulated protein Kinases 1 and 2 (ERK1/2) that stimulate the phosphorylation of tyrosine hydroxylase, the rate-limiting enzyme for dopamine biosynthesis. We therefore set out to test the hypothesis that human ser (A) homozygotes would show elevated dopamine synthesis capacity compared with cysteine (cys) homozygotes and heterozygotes (TT and AT) for rs821616. [ 18 F]-DOPA positron emission tomography (PET) was used to index striatal dopamine synthesis capacity as the influx rate constant Ki cer in healthy volunteers DISC1 rs821616 ser homozygotes ( N = 46) and healthy volunteers DISC1 rs821616 cys homozygotes and heterozygotes ( N = 56), matched for age, gender, ethnicity and using three scanners. We found DISC1 rs821616 ser homozygotes exhibited a significantly higher striatal Ki cer compared with cys homozygotes and heterozygotes ( P = 0.012) explaining 6.4% of the variance (partial η 2 = 0.064). Our finding is consistent with its previous association with heightened activation of ERK1/2, which stimulates tyrosine hydroxylase activity for dopamine synthesis. This could be a potential mechanism mediating risk for psychosis, lending further credibility to the fact that DISC1 is of functional interest in the aetiology of major mental illness.